The development of the system for automatic design of rotational parts - Gatalo, Ratko; Navalušić, Slobodan (Journal of Production Engineering, 1986)
The paper deals with a system for automatic design of rotational parts with technical drawing as an exit. Only basic informations have been presented about modules of the system processor. Particulary are presented informations about testing results obtained on computer. EI-H6/43 and graphic terminal TEKTRONIX 4010. The paper presents a part of the results of the several years research project at the Institute for Production Engineering of Faculty of Technical Sciences in Novi Sad.